Resilience and anxiety in nurses in a hospital in Iran during the COVID-19 pandemic: a cross-sectional study - Askarpour, Hedyeh; Davarani, Esmat Rezabeigi; Dahooiyeh, Alireza Baniasadi; Faryabi, Reza; Goharrizi, Mohammad Ali Sheikh Beig; Oruei, Sara; Daneshi, Salman (Acta Scientiarum. Health Sciences, 2023)
The lack of any definitive treatment or prevention of COVID-19 disease has created a lot of stress and anxiety in societies. This study aimed to evaluate the resilience and anxiety of COVID-19 in nurses of Imam Khomeini Hospital in Jiroft and their relationship with demographic variables from April to August 2020. The present study is descriptive-analytical and cross-sectional. To select the statistical sample, the census method was used so that 80 nurses working in different wards of the hospital were selected and included in the study. The resilience measurement tool is the Connor-Davidson Resilience Questionnaire (CD-RIS). COVID-19 anxiety was assessed using a comprehensive national questionnaire. Data were analyzed using descriptive and analytical statistics Chi-square, Independent two-sample parametric t-test, and ANOVA through SPSS 20. The level of COVID-19 anxiety in nurses was moderate (19.3±11.64) and the rate of resilience was low (36.7±16.65). There is a statistically significant difference between resilience in nurses and age (p = 0.003). There was no statistically significant relationship between the rate of resilience in nurses and gender (p = 0.13), the unit of service (p = 0.87), marital status (p = 0.98), work experience (p = 0.06), and the level of education (p = 0.63). There was no statistically significant relationship between anxiety in nurses and age (p = 0.53), gender (p = 0.59), the unit of work (p = 0.48), marital status (p = 0.90), work experience (p = 0.40), and level of education (p = 0.60). The results of multivariate analysis showed that, work experience, and place of work have a statistically significant relationship with resilience and anxiety of COVID-19 in nurses, respectively (p <0.05).The level of COVID-19 anxiety in nurses is moderate and the rate of resilience is high. Given the current high-risk situation, it is important to identify nurses prone to psychological disorders to maintain and improve their mental health with appropriate strategies and techniques.